PERAN BANK SAMPAH BUMI INSPIRASI SEBAGAI UPAYA MEMBERDAYAKAN MASYARAKAT DALAM MENDUKUNG KEBIJAKAN KANG PISMAN - Andika Pratama; Nunu Heryanto; Joni Rahmat Pramudia (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2021)
The waste problem is a classic problem that is quite difficult to solve. This article aims to discuss the role of the bank sampah Bumi Inspirasi as an effort to empower the community in supporting the KANG PISMAN policy. This research method uses a qualitative descriptive approach using a logical analysis model. The findings show that the community empowerment carried out by the bank sampah Bumi Inspirasi has been carried out in a sustainable manner and with sufficiently optimal results, but is still constrained by several obstacles such as a lack of infrastructure and support from the government and the private companies. The implication of this finding is that the bank sampah is one of the institutions that will strongly support government programs in realizing less waste city if the cooperation between stakeholders is well established.Keywords: Community Empowerment, Bank Sampah, Waste Management